Effect of Gandaria Ethanol Extract on Electrolytes and Kidney in CCl₄-Induced Rats - Ridhayana Syaharani; Husnarika Febriani (Universitas Nusa Bangsa, 2026)
Carbon tetrachloride (CCl₄) is a toxic chemical widely used in industry and known to cause oxidative stress and kidney damage through reactive oxygen species (ROS) production. This study aimed to investigate the protective effect of ethanol extract of Gandaria fruit (Bouea macrophylla Griff.) on kidney function by assessing serum electrolyte levels and kidney histology in white rats (Rattus norvegicus L.) induced with CCl₄. Twenty-five male rats were divided into five groups: normal control, CCl₄ control, and three treatment groups receiving 100, 150, and 200 mg/kg body weight of Gandaria extract. CCl₄ was administered intraperitoneally at 1 mL/kg every 72 hours for 30 days, while the extract was given orally from day 8 to 30. CCl₄ induction significantly increased serum Na⁺, K⁺, and Cl⁻ levels and caused histopathological changes including glomerular enlargement, vacuolization, and necrosis in kidney tissue. Gandaria extract administration significantly (p<0.05) reduced electrolyte imbalance and improved kidney tissue structure in a dose-dependent manner. The highest dose (200 mg/kg) showed the strongest protective effect, with parameters nearing normal control levels. These results suggest that the Gandaria fruit extract shows promising nephroprotective properties, likely due to its content of secondary metabolite compounds, which could have potential therapeutic implications for preventing chemical-induced kidney damage.